APPRAISAL OF ACADEMIC PERFORMANCE OF MALE AND FEMALE SCIENCE – BASED GRADUATES ADMITTED THROUGH UTME ONLY AND UTME/POST-UTME IN NNAMDI AZIKIWE UNIVERSITY, AWKA (NAU Journal of Technology and Vocational Education, 2024)
The cardinal focus of this study is to examine the impact of modes of admission (UTME and Post-UTME) on academic performance of male and female in science related disciplines in Nnamdi Azikiwe University, Awka. It was an ex-post facto research design. Three research questions and three null hypotheses guided the study. The study covered eight academic sessions, four years before the introduction of Post-UTME from 2001 – 2005 and four years after the introduction of Post-UTME from 2005 – 2009. The population of the study was 35,308. The sample was 1928 drawn from the department following the admission and registration lists of those who were admitted through UTME only and those admitted through UTME / Post-UTME respectively. Two instruments were used for data collection, which included Admission list and student’s academic records. Mean statistics was used to analyze the research question while the null hypothesis was tested using z-test at 0.05 level of significance. The finding revealed the following; the academic performance of male science graduates was higher than the female sciences graduates admitted either from the two modes of entry. Based on the finding the study recommended among others that; equal representation of both genders should be ensured during admission especially in sciences related disciplines. Also post –UTME should be reinstated as a  functional screening exercise for admission into Nigerian universities.
Keywords: Education; Academic Performance; FCGPA; UTME; POST-UTME, Gender, Science discipline